Regulation of the MIE Locus During HCMV Latency and Reactivation - Abigail L. Dooley; Christine M. O’Connor (Pathogens, 2020)
Human cytomegalovirus (HCMV) is a ubiquitous herpesviral pathogen that results in life-long infection. HCMV maintains a latent or quiescent infection in hematopoietic cells, which is broadly defined by transcriptional silencing and the absence of de novo virion production. However, upon cell differentiation coupled with immune dysfunction, the virus can reactivate, which leads to lytic replication in a variety of cell and tissue types. One of the mechanisms controlling the balance between latency and reactivation/lytic replication is the regulation of the major immediate-early (MIE) locus. This enhancer/promoter region is complex, and it is regulated by chromatinization and associated factors, as well as a variety of transcription factors. Herein, we discuss these factors and how they influence the MIE locus, which ultimately impacts the phase of HCMV infection.